2009
DOI: 10.1093/sleep/32.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work Disorder Among Oil Rig Workers in the North Sea

Abstract: The prevalence of SWD was relatively high among these shift workers. Individuals with SWD reported poorer sleep quality and more subjective health complaints in the non-work period than shift workers not having SWD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
151
4
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(170 citation statements)
references
References 23 publications
12
151
4
3
Order By: Relevance
“…We found that the prevalence of SWD among these workers was 62.8% in our sample, which is very high compared with the rates found by other studies using the same criteria for SWD [5,6,8]. The participants in the study conducted by Di Milia L et al [5] were drawn from the community and worked various types of shift, including some involving few nights, which may explain the low prevalence reported by that study.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…We found that the prevalence of SWD among these workers was 62.8% in our sample, which is very high compared with the rates found by other studies using the same criteria for SWD [5,6,8]. The participants in the study conducted by Di Milia L et al [5] were drawn from the community and worked various types of shift, including some involving few nights, which may explain the low prevalence reported by that study.…”
Section: Discussioncontrasting
confidence: 49%
“…The participants in the study conducted by Di Milia L et al [5] were drawn from the community and worked various types of shift, including some involving few nights, which may explain the low prevalence reported by that study. In contrast, the participants in a research conducted by Waage S et al [6] followed a slow rotation shift schedule. It is possible that rapidly rotating shift work tends to cause sleep disorders because of its association with a reduction in the total duration of sleep [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations